RELEVANSI NILAI INKREMENTAL ARUS KAS OPERASI DAN LABA (EARNING AFTER TAX) TERHADAP HARGA SAHAM (Study Kasus di Perusahaan Manufaktur yang terdaftar di Bursa Efek Indonesia (BEI) periode 2015-2017) - Fatimatus Zuhairoh; Tony Seno Aji; Meta Ardiana (Universitas Muhammadiyah Malang, 2019)
The aim of the study was to prove empirically the effect of net income after taxand operating cash flow on stock prices in the BEI-listed manufacturing companies for the period 2015-2017 and to see whether there was an incremental relevance given by the two independent variables to the dependent variable. The object of the research was carried out on manufacturing companies listed on the IDX for the period 2015-2017. The sample selection method used was purposive sampling and the selected sample amounted to 77 manufacturing companies multiplied by 3 years to number 231 company data. This study uses secondary data and is assisted by the SPSS version 16.0 statistical test. The results of the study show that cash flow from operations have incremental value relevance to closing price stock, as like the cash flow from operations, Earnings after tax have incremental value relevance to closing price stock too. Conclusions from the research show that both of cash flow from operations dan earning after tax have incremental value relevance to closing price stock. Keywords:Value Relevance, Incremental Value, Operating Cash Flow, Earning After Tax, Stock Price.